Exploring the Application of Bifunctional Metal Chelators in Treating Triple-Negative Breast Cancer - Li, Kuo; Zhang, Youjiu; Wang, Xiaomei; Zhu, Ran; Ma, Changsheng; Hu, Rui (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose In this study, we independently synthesized and labelled a novel bidentate bifunctional chelating agent, 177Lu-3,4-HOPO-Cetuximab, that achieved tight binding between targeting and radioactivity, and evaluated its targeted killing ability of cells in vitro and in vivo. Method 3,4-HOPO was successfully synthesized through a series of chemical steps using malt phenol as the raw material, which was then coupled with Cetuximab and labelled with 177Lu. 177Lu-3,4-HOPO-Cetuximab was tested for its cell viability and cell binding rate after different times and at different doses by CCK-8 and cell binding experiments. 177Lu-3,4-HOPO-Cetuximab (approximately 500 μCi) was injected into the tail vein of a subcutaneous metastasis mouse model of triple-negative breast cancer with a single injection, and tumour volume growth and body weight changes were regularly monitored for 20 days. The radioactivity distribution in nude mice was analysed after sacrifice, and the treated and untreated tumour tissues were analysed by HE staining. Result The cell viability of 177Lu-3,4-HOPO-Cetuximab declined exponentially after treatment for 48 h at 500 Bq/mL to 5 MBq/mL, respectively; the cell activity of /mL was slowed down after 8h to 96h at a dose of 5 MBq; while the binding rate of 4T1 cells in 177Lu-3,4-HOPO-Cetuximab after 1h to 24h respectively increased logarithmically. After 20 days of treatment, the body weight of nude mice in the 177Lu-3,4-HOPO-Cetuximab group didn’t change, but the body weight of the control group decreased significantly. The tumor inhibition rate of the 177Lu-3,4-HOPO-Cetuximab group was (37.03±11.16)%; HE staining showed that tumor cells were affected by the action of 177Lu causing necrosis. Conclusion The experiments showed that 177Lu-3,4-HOPO-Cetuximab has a certain targeted therapeutic ability for triple-negative breast cancer, and it is expected to become a potential targeted nuclear medicine treatment for triple-negative breast cancer.